2021
DOI: 10.3389/fpls.2021.679726
|View full text |Cite
|
Sign up to set email alerts
|

Response of Leaf Traits of Eastern Qinghai-Tibetan Broad-Leaved Woody Plants to Climatic Factors

Abstract: Plant ecologists have long been interested in quantifying how leaf traits vary with climate factors, but there is a paucity of knowledge on these relationships given a large number of the relevant leaf traits and climate factors to be considered. We examined the responses of 11 leaf traits (including leaf morphology, stomatal structure and chemical properties) to eight common climate factors for 340 eastern Qinghai-Tibetan woody species. We showed temperature as the strongest predictor of leaf size and shape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…5a, b). Kang et al (2021) noted that plants tend to balance light capture with damage from high solar radiation. Solar radiation increased with increasing aridity on the LP and MP (Table S6).…”
Section: Interacting Effects Of Abiotic and Biotic Factors On The Var...mentioning
confidence: 99%
See 2 more Smart Citations
“…5a, b). Kang et al (2021) noted that plants tend to balance light capture with damage from high solar radiation. Solar radiation increased with increasing aridity on the LP and MP (Table S6).…”
Section: Interacting Effects Of Abiotic and Biotic Factors On The Var...mentioning
confidence: 99%
“…Communities change their morphological functional traits to tolerate environmental stress, including leaf area (LA) and specific leaf area (SLA) (Wright et al, 2017). LA and SLA determine a plant's capacity to capture light (Poorter et al, 2009), leaf heat exchange (Wright et al, 2017), and the length of the water pathway through leaves (Kang et al, 2021) -all of which are closely related to transpiration and photosynthesis. Previous studies have focused primarily on the patterns of LA and SLA along environmental gradients (Peppe et al, 2011;Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Take leaf physiological traits for an example, several studies have revealed that simultaneous measurement of both LWC and δ 13 C provides a better understanding water use efficiency (WUE) response towards a reducing water supply in native species growing in arid or semi-arid environments ( Chen et al., 2007 ; Bouda et al., 2013 ; Easlon et al., 2014 ). Several studies have reported that species with higher SLA always pair with higher leaf N and P concentrations, these acquisitive traits result in a faster return on resource investment and promote rapid plant growth ( Wright and Cannon, 2001 ; Wright et al., 2004b ; Kang et al., 2021 ). On the contrary, the slow return on investments and growth rate result from more conservative traits combinations, for example, lower SLA with lower leaf elements traits and their stoichiometric characteristics ( Kang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that species with higher SLA always pair with higher leaf N and P concentrations, these acquisitive traits result in a faster return on resource investment and promote rapid plant growth ( Wright and Cannon, 2001 ; Wright et al., 2004b ; Kang et al., 2021 ). On the contrary, the slow return on investments and growth rate result from more conservative traits combinations, for example, lower SLA with lower leaf elements traits and their stoichiometric characteristics ( Kang et al., 2021 ). Accordingly, exploring the trait-trait relationships provide a better understanding of how plants develop a suite of trait combinations that enable them to adapt to native habitats.…”
Section: Introductionmentioning
confidence: 99%